The Production of Health in the Amazonian Liquid Territory: Reflections on Riverine Primary Healthcare Units over the First 10 Years - Maria Adriana Moreira; Fabiana Mânica Martins; Vanessa Colares Magalhães Alves; Geisy de Andrade Lima; Josiane de Souza Medeiros; Júlio César Schweickardt (Saúde e Sociedade, 2025)
Abstract The text aims to analyze the National Primary Health Care Policy (PNAB) with a focus on the regions of the Legal Amazon and the Pantanal, using the experience of the Fluvial Basic Health Units (UBSF) as a reference. The data were produced through the cartographic method, a narrative and reflective writing of praxis in research, management, and assistance in the Amazon. The authors produce this narrative as participants, starting from the inauguration of the first UBSF in Borba, Amazonas, in 2013, financed by the Ministry of Health. The authors are engaged in Permanent Health Education in action for the Amazon. For the analysis, the theoretical assumption of the liquid territory was used, a category developed by the authors that enhances the understanding of the region. It is evident that there are more than 30 active boats in the country, which increases access to health for riverside populations; moreover, the promotion of comprehensiveness and equity in the care offered to communities is observed. Challenges remain: the financing of these units and the need for continuous permanent education actions for professionals, aiming at health promotion that respects the specificities of the liquid territory of the Amazon.